STUDY OF SERUM URIC ACID LEVELS IN PREGNANCY INDUCED HYPERTENSION - DR. LAXMI NARAYANA S,; DR. M. D. SULEMAN,; DR. B. VODELU, (International Journal of Pharma and Bio Sciences, 2014)
The aim of the present study is to understand and investigate the association/relationship of selected physical and biochemical parameters among pregnant women with hypertension and without hypertension. The 54 cases were selected from the antenatal outpatient, Gandhi Hospital, Secunderabad, Telangana state with age group between 18-24 years, primigravide with known last menstrual period and gestational age between 20-30 weeks. Among 54 women, 36 were pregnancy induced hypertensive, considered as experimental group and remaining 18 were normotensive taken as control group. The experimental group was further categorized into three groups based on the degree of hypertension. Serum Uric Acid levels had significantly increased only in the group-3 of experimental group, but not in the group- 1 & 2. This observation clearly suggests that as the diastolic blood pressure increases, serum Uric Acid levels also increase, thereby resulting in an increased risk of adverse pregnancy outcomes. Based on the present study results, it can be suggested that serum Uric Acid levels can act as a good marker for early detection of pregnancy induced hypertension.